2020
DOI: 10.1182/blood.2020005819
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants for cancer-associated venous thromboembolism: a systematic review and meta-analysis

Abstract: Direct oral anticoagulants (DOACs) are an emerging treatment option for cancer patients with acute venous thromboembolism (VTE), but studies have reported inconsistent results. This systematic review and meta-analysis compared the efficacy and safety of DOACs and low-molecular-weight heparins (LMWH) in these patients. MEDLINE, Embase, CENTRAL, and conference proceedings were searched to identify relevant randomized controlled trials. Additional data were obtained from the original authors to homogenize definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 30 publications
2
93
0
6
Order By: Relevance
“…Caution should be applied to patients with cancer‐ and CVC‐related UEDVT, due to the high risk of bleeding 68 . A recently published meta‐analysis of RCTs evaluating cancer‐associated usual‐site VTE showed a (nonsignificant) lower risk of recurrent VTE, balanced by a (nonsignificant) higher risk of MB with the DOACs compared to LMWH, 112 thus supporting the use of the DOACs also in patients with cancer. However, certain conditions (such as GI or genitourinary tumors or CNS metastasis) carry a particularly high bleeding risk, and these patients may not be candidates for DOACs.…”
Section: Practical Advice Regarding Doacs In Unusual‐site Vtementioning
confidence: 94%
“…Caution should be applied to patients with cancer‐ and CVC‐related UEDVT, due to the high risk of bleeding 68 . A recently published meta‐analysis of RCTs evaluating cancer‐associated usual‐site VTE showed a (nonsignificant) lower risk of recurrent VTE, balanced by a (nonsignificant) higher risk of MB with the DOACs compared to LMWH, 112 thus supporting the use of the DOACs also in patients with cancer. However, certain conditions (such as GI or genitourinary tumors or CNS metastasis) carry a particularly high bleeding risk, and these patients may not be candidates for DOACs.…”
Section: Practical Advice Regarding Doacs In Unusual‐site Vtementioning
confidence: 94%
“…The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1. Within each category of meta‐analysis (two, three, or 4 RCTs), the results were similar regarding the risks of VTE recurrence (differences in pooled relative risks ranging from 0 to 0.08) and major bleeding, except for one of the 11 meta‐analysis of four RCTs 24 that did not confirm a statistically significant reduction of VTE recurrence risk with DOACs compared with LMWH (Figure 1). The small differences observed between the results of the meta‐analyses can be attributed to minor methodological differences such as the method of data extraction (from the original number of events or form reported hazard ratios), the length of follow‐up (up to 12 months in one RCT, 6 months in the other three RCTs), the choice of denominators, or the definition of the clinical events taken into account for the analysis (see details in Table 1).…”
Section: Resultsmentioning
confidence: 90%
“…At the time the search was ended (October 6, 2020), 46 records were identified, of which 26 were discarded on title and abstract ( n = 24) or full‐text ( n = 2). The 20 remaining meta‐analyses were published in nonpredatory peer‐reviewed journals: five studies pooled the data of two RCTs, 6‐10 four studies pooled the data of three RCTs, 11‐14 and 11 studies pooled the data of four RCTs 15‐25 . The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with respect to DOACs vs LMWH, besides SELECT-D trial [37], six meta-analyses indicated that DOACs were more efficacious in the treatment of cancer-associated VTE with an increase of bleeding risk, compared with LMWH [11,20,[38][39][40][41], whereas a retrospective study [7] and another five meta-analyses [10,15,16,42,43] indicated that DOACs were more efficacious with a comparable bleeding risk, compared with LMWH. In the ADAM VTE trial, major bleeding and VTE recurrence rates were both lower in cancer patients with VTE receiving oral apixaban than those receiving dalteparin [44].…”
Section: Doacs Vs Lmwhmentioning
confidence: 99%